Exploring the Opportunities and Challenges of Mr. Taufiq's Grocery Store Business: reviewed from the aspect of business management with a SWOT approach in Kombangan Village - Saiful Arif; Abdur Rahman (Penerbit Hellow Pustaka, 2025)
Despite the prevalence of SWOT analysis in business management literature, there is a paucity of studies focusing on its application in the context of small-scale enterprises, particularly in rural areas such as Desa Kombangan. This research aims to bridge this gap by investigating how Mr. Taufiq's grocery store navigates its business environment using the SWOT approach.Focus and Research Objective: This study aims to examine the opportunities and challenges faced by Mr. Taufiq's grocery store in Desa Kombangan through the lens of business management, utilizing the SWOT analysis framework. The primary objective is to identify key factors influencing the business's performance and develop strategic insights to enhance its competitiveness.Methodology: Employing a qualitative research approach, data was collected through semi-structured interviews with Mr. Taufiq, observation of daily operations, and analysis of relevant documents. The SWOT analysis method was utilized to systematically assess the internal strengths and weaknesses as well as external opportunities and threats of the business.Results: The findings reveal a range of opportunities, including growing demand for convenience shopping and a loyal customer base, alongside challenges such as competition from larger retailers and supply chain disruptions. Through SWOT analysis, strategic recommendations were formulated to capitalize on strengths, address weaknesses, leverage opportunities, and mitigate threats, thereby enhancing the resilience and sustainability of Mr. Taufiq's grocery store in Desa Kombangan.